The effects of magnetic and radiometric responses on hydrothermal zones and its implication in minerals characterization over part of Nasarawa, North Central Nigeria (Journal of Tropical Resources and Sustainable Science (JTRSS), 2023)
Airborne magnetic and radiometric data set over part of Nasarawa, North central Nigeria have been enhanced and interpreted qualitatively. Attributes maps (first and second vertical derivative; and analytic signal maps) from the total magnetic intensity map (TMI) were used to delineate near-surface structures hosting sedimentary rocks forming minerals and differentiate regions based on amplitude responses. The structure trends NE-SW, NW-SE, E-W and N-S directions and the area is predominantly underlain by basement and sedimentary outcrops in the northeastern/western, central portion and southern parts respectively. The total cout map showed the low, moderate and high levels ranged from 6.40 to 14.70 ?R/h, 13.31 to 16.66 ?R/h and 18.02 to 41.23 ?R/h respectively. The Potassium concentration revealed the lowest concentration level (0.02-0.0.16%), moderate level (0.17-0.47%) and highest concentration of (18–27%). The lowest concentration level in the eTh map is related to siltstones and sandstones (Ansh), shale and mudstones (Nsh) and sandstone. The highest level reaches 31.35 ppm in volcanics rocks. The equivalent Uranium concentration map (eU) indicates that the high level of uranium concentration is associated with the black shales, siltstones and sandstones (Ansh) while shale and mudstones (Nsh), sandstones, shale and sandy clay (LaSS), sandstones (Ess), shale and limestones (Esh) and alluvium deposition has the lowest one. The potassium thorium ratio map shows zones characterized by the high K/eTh ratio values that are strong indicators of hydrothermal alteration. From the K/eTh ratio map, it can be observed that the areas affected by the hydrothermal process are featured in pink colour and have a high value of 0.37 in the K/eTh ratio which is an indication of gold mineralisation.
Keywords: minerals; hydrothermal zones; basement and sedimentary outcrops; Centre for Exploration Targeting (CET); first vertical derivatives(FVD); second vertical derivatives (SVD); total count